Numerical simulation of flow past a curved cylinder in uniform and logarithmic flow. (3rd April 2017) - Xu, Tianyu; Cater, John E.
Abstract : This research presents a computational fluid dynamics study for simulating a curved cylinder in ocean currents. A rigid curved cylindrical geometry with two bending directions was modelled in uniform and logarithmic flow profiles at a maximum Reynolds number of 1.5 × 10 5 ; the Realizable k –epsilon formulation is used as the turbulence closure model. An analysis of force coefficients and vortex structure are presented. The results show that a curved cylindrical structure will have different hydrodynamic behaviour depending on the oncoming flow direction. Bending the cylinder in a direction which is opposite to the predominant flow direction is recommended, as the maximum forcing amplitude is reduced in this case.